Job Maintenance by Supported Employment: An Overview of the “Supported Employment Plus” Trial - Kawohl, Wolfram; Moock, Jörn; Heuchert, Sandra; Rössler, Wulf (Frontiers in Public Health, 2015)
The number of days of absence from work associated with mental illness has risen dramatically in the past 10 years in Germany. Companies are challenged by this issue and seek help for the physical and mental health of their employees. Supported Employment concepts such as the Individual Placement and Support (IPS) model have been designed to bring jobless persons with mental disorders back to work. In the randomized, controlled SEplus trial, a modified IPS-approach is tested concerning its ability to shorten times of sick leave of persons with mental distress or a mental disorder and to prevent them from losing their job. The trial is outlined in this study protocol.